2010
DOI: 10.1002/path.2738
|View full text |Cite
|
Sign up to set email alerts
|

Variations in stromal signatures in breast and colorectal cancer metastases

Abstract: The tumor microenvironment (TME) plays an important role in tumor survival and growth but little is known about the degree of preservation between different stromal response patterns found in primary tumors and their metastases. We have previously identified gene expression profiles for two distinct stromal signatures in breast carcinoma of fibroblast (aka DTF) and macrophage response (aka CSF1) and found them to be correlated with clinicopathologic features including outcome. In this study, we compare the DTF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
2
25
0
1
Order By: Relevance
“…These experimental data combined with the positive correlation between CSF-1 levels, macrophage recruitment and poor prognosis in human cancers (Scholl et al 1994;Leek and Harris 2002), together support the notion that macrophages and/or their products play a major role in facilitating late-stage metastatic progression of tumors (Lin et al 2001). Significantly a stromal CSF-1 gene expression signature in breast cancer correlated with poor outcomes and was observed to be similar between primary tumors and lymph node metastases (Webster et al 2010).…”
Section: Leukocytes In Mammary Development and Cancermentioning
confidence: 62%
“…These experimental data combined with the positive correlation between CSF-1 levels, macrophage recruitment and poor prognosis in human cancers (Scholl et al 1994;Leek and Harris 2002), together support the notion that macrophages and/or their products play a major role in facilitating late-stage metastatic progression of tumors (Lin et al 2001). Significantly a stromal CSF-1 gene expression signature in breast cancer correlated with poor outcomes and was observed to be similar between primary tumors and lymph node metastases (Webster et al 2010).…”
Section: Leukocytes In Mammary Development and Cancermentioning
confidence: 62%
“…First, mainly due to poor experimental conduct, false (derived from another cell population within the cell culture than the one intended), cross-contaminated (with other human cells or cells from other species) and/or pathogen-(mycoplasm) contaminated cell lines have been discovered repeatedly. [9][10][11][12] Second, the representativeness of cultured cell lines as compared with the original tumors is being questioned as these cells have been cultured in the absence of stroma, 13 hence lacking the proper microenvironment and the original tissue architecture. Moreover during culturing, specific cells are continuously selected based on the in vitro conditions and cells might undergo additional ex vivo mutations.…”
mentioning
confidence: 99%
“…Recently, a concordance between the CSF1 macrophage response signature in primary mammary and colorectal carcinomas and their corresponding lymph node metastases has been reported. 30 In a previous study, we also encountered a positive correlation between CD163-macrophages in primary endometrioid endometrial carcinomas and their matched lymph node metastases. 31 In the current study, we found that the expression of CSF1 by the tumor cells of primary endometrioid endometrial carcinomas is maintained in most metastatic tumors.…”
Section: Discussionmentioning
confidence: 99%